Chiral double helical silver complexes: subcomponent self-assembly and self-sorting. (28th January 2016) - Zhang, Feng-Li; Tian, Lei; Qin, Long-Fang; Chen, Jia-Qian; Li, Zaijun; Ren, Xuehong; Gu, Zhi-Guo
Graphical abstract: Four novel homochiral dinuclear Ag(I) complexes have been successfully synthesized by subcomponent self-assembly. Highly selective narcissistic self-sorting behavior was observed in the self-assembly process of the Ag helicates from a mixture of similar components that only alkyl chain different. This was confirmed by overlaying the 1 H NMR of the mixture with the individually synthesized chiral helicates. Abstract: Four homochiral dinuclear complexes, namely, [Ag2 (LC4 )2 ](OTf)2 (1 ), [Ag2 (LC4 )2 ](ClO4 )2 (2 ), [Ag2 (LC5 )2 ](OTf)2 (3 ), [Ag2 (LC5 )2 ](PF6 )2 (4 ) have been successfully synthesized from subcomponent self-assembly of imidazole-2-carboxaldehyde derivatives, R -phenylethylamine and silver salt. LC4 and LC5 were flexible ligands, containing the same imidazole Schiff-bases coordination motif and varying in alkyl chain lengths with four and five carbon atom, respectively. Single crystal structures revealed that the silver(I) center in1 –4 coordinated with 4 N donor atoms from two symmetrical chiral ligands assuming Δ configuration with a tetrahedral coordination environment. [Ag2 (LCn )2 ] 2+ components all presented double helical structures exhibiting only P -handedness with Ag–Ag, π–π, and C–H⋯π intramolecular interactions. Highly selective narcissistic self-sorting behavior can be observed during the self-assembly of1 and3 .